Progress on Financial and Corporate Restructuring : East Asia Update - Ghosh, Swati (World Bank, Washington, DC, 2020)
Growth in East Asia, including that of the crisis-affected countries has strengthened progressively-despite the magnitude of the shocks experienced during the financial crisis and their effects on the balance sheets of financial institutions and corporates. Progress on financial and corporate restructuring has contributed to the consolidation of growth. Indeed. Countries that have made the most progress on corporate and financial sector restructuring, notably Korea and Malaysia-have experienced the strongest growth performance since the crisis. However, growth has not been sufficient to redress the problems in the balance sheets of financial and corporate sectors. Although progress has been made in reducing vulnerabilities, especially in the banking sector, progress on corporate restructuring has been slower and more uneven across countries. In most countries, debt-to-equity ratios remain high relative to international norms and continue to pose a threat in the event of a major shock. A sustained effort is needed to complete the corporate and financial sector restructuring agenda, especially since the cases that remain are the more difficult ones. Such efforts are important not only to further potential vulnerability in the kind of uncertain global economic environment we are witnessing, but also to position East Asia for productivity-led growth that must be the basis for sustained improvements in income over the longer-term.